INTERNATIONAL ELECTRONIC STOCK TRADING: MECHANISM OF FUNCTIONING AND CURRENT TRENDS (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Abstract. Modern international electronic stock trading is becoming increasingly important in the organization of the system of international trade relations. Several studies of the domestic and foreign scientists have highlighted various aspects of the place and role of electronic exchanges in trade relations between countries. At the same time, the peculiarities of the mechanism of functioning of the international e-commerce, which is constantly evolving and improving, need to be studied both from the point of view of theory and practice.Electronic exchanges have created and implemented their own mechanism of functioning, which turns them into the most organized form of international trade. It is substantiated that trends and key features of the development of electronic exchanges can be tracked and forecasted with the help of relevant stock indices. The main features and the most important aspects of the development of electronic exchanges are determined, based on the analysis of stock indices of the two largest electronic exchanges in the world, the geographical structure of electronic stock exchanges and the dynamics of the use of artificial intelligence in the exchange trading process. Here also highlighted the negative and positive interdependencies regarding the future development of international e-commerce.
Keywords: electronic exchanges, stock exchange trade, stock indices, mechanism of functioning of international electronic exchange trading, trends of international electronic exchange trade